Meso-Alpha Scale Tropospheric Interactions within the Western Mediterranean Basin: Statistical Results Using 15-Year NCEP/NCAR Reanalysis Dataset - J. L. Palau; F. Rovira (Advances in Meteorology)
After a 15-year average of the reanalyses meteorological data provided by NCEP/NCAR, this paper shows the mean seasonal evolution, between April and October, of the tropospheric dynamics in the Western Mediterranean Basin (WMB). As shown in this paper, it is the result of the meso-alpha interaction between the daily oscillation of coastal thermally driven circulations around the basin and the daily pulsation of sinking speeds over areas of the Western Mediterranean Sea. Furthermore, from the 15-year average, a statistically significant correlation has been found between these processes (the daily oscillation of sea breezes and the daily pulsation of subsidence/convergence on the WMB). The quantification of this persistent link between these tropospheric processes elucidates their teleconnection at the meso-alpha scale and the seasonal evolution of the strength of this linkage. Test statistics are greater than critical values for the 5% significance level of the F-distribution. Besides, we have estimated a generalised diurnal compensatory subsidence over the Western Mediterranean Sea with a maximum mean sinking (subsidence) motion of up to −0.2 cm/s at 18:00 h UTC and 1000 hPa and a nocturnal generalised mean upward (convergence) motion of up to 0.05 cm/s at 00:00 h UTC and 1000 hPa.